From participation roles to socio‐emotional information roles: Insights from the closure of an online community. (10th June 2022) - Karanasios, Stan; Zorina, Aljona
Abstract: This study examines what happens when an online community (OC) platform is shut down. In particular, it builds on recent interest from information science on everyday life information seeking, providing insights into the socio‐emotional roles enacted by users following community closure. A qualitative study is undertaken on 12 months of social media comments relating to the closure of an OC platform. We identify and discuss the socio‐emotional information roles that manifest, and present a model of their relationship to different aspects of the closure. We make theoretical connections between the notion of socio‐emotional information roles and both the information behavior and practice literature, as well as research on community and participant roles. Theoretical and practical implications are discussed.